ISDS Reform UNCITRAL: Implications For Indonesian Investment Policy - Wiko, Garuda; Kinanti, Fatma Muthia (Faculty of Law Universitas Lampung, 2024)
The United Nations Commission on International Trade Law (UNCITRAL) Working Group III (WG III) has been meeting intensively to formulate comprehensive reforms to Investor-State Dispute Settlement (ISDS) based on emerging criticisms. In July 2017, UNCITRAL established Working Group III with a mandate to identify and evaluate ISDS-related concerns, consider the need or desirability of reforms, and develop relevant solutions. Some of the issues that have been identified in relation to the current ISDS mechanism include lack of consistency and predictability of arbitral awards by ISDS forums, lack of independence and impartiality of arbitrators, cost and duration of proceedings, and third-party financing. The WG III forum has formulated several options to address these issues: 1) establishment of a court mechanism, 2) appointment of arbitrators and adjudicators, 3) parties' involvement and control, 4) dispute prevention and mitigation: strengthening dispute prevention and mitigation mechanisms, 5) cost management and third-party financing transparency: efforts to manage costs and related procedures, as well as transparency in third-party financing. The findings indicate that Indonesia actively participates in WG III by advocating for balanced reforms that safeguard state sovereignty and public interest while addressing investor rights. Key recommendations include enhancing transparency and leveraging regional alliances to strengthen Indonesia’s position in international investment frameworks.